A data-driven methodology for non-invasive tempearture estimation in multilayered media - Teixeira, C. A. (2013)
A main limitation on the application of thermal therapies is the lack of quantitative temperature knowledge in the treatment zone. This knowledge would increase the safety and effectiveness, through a correct instrumentation control. The portability and relative low cost of the ultrasound devices encourages the application of backscattered ultrasound (BSU) for temperature estimation. So far the methods based on BSU were only developed for homogeneous media. This paper reports a data-driven methodology able to estimate temperature in non-homogeneous media, with the required resolution. Appropriate generalisation performance was observed even under operating situations never considered in the training procedure.